Current status of drugs in development for celiac disease. (August 2014) - Kurppa, Kalle; Hietikko, Minna; Sulic, Ana-Marija; Kaukinen, Katri; Lindfors, Katri
<x xml:space="preserve">Abstract</x> Introduction: Gluten is the main trigger for celiac disease, and the current treatment is based on its elimination from the diet. Although the symptoms usually disappear during the diet, it is restrictive and difficult to maintain. Further, despite a strict treatment the small-bowel mucosal damage does now always heal. Consequently, adherence is often poor and new treatment approaches are needed. With an increased understanding of the disease pathogenesis, several novel treatments have been suggested, and some of them have already entered Phase II clinical trials. Areas covered: This article reviews the latest status of the drugs in development for celiac disease. The article focuses mainly on synthetic drugs currently entering in clinical trials. Expert opinion: It is anticipated that some of the treatments under investigation will soon enter Phase III clinical trials, although challenges remain. For instance, histological studies are problematic in wide-scale clinical studies. On the other hand, the existing non-invasive serological methods and clinical outcome measures might be too insensitive for monitoring responses to the possible drug candidates. There is also no animal model which would accurately reflect celiac disease. Well-conducted basic and clinical research is required to develop better non-invasive surrogate markers and patient-related outcomes for future pharmacological studies.